Systematic Review of Spinal Cord Injuries in Equestrian Athletes: Incidence, Risk Factors, and Outcomes - A. Heinrich Emily; D. Crane Kayleigh; I. Chiaramonti Nicholas; Rossignol Julien; Wolohan Michael (Journal of Sports and Exercise Medicine, 2025)
Objective The goal of this systematic review is to identify common themes amongst acute spinal cord injuries (SCI) in equestrian athletes. Design A systematic review was performed using PubMed, CINAHL Plus with Full Text (EBSCO), Cochrane Library, and Scopus with pre-determined MESH terms. The initial search returned 354 studies. Following PRISMA guidelines, 13 articles were included. Exclusion criteria included injuries to the horse only, non-English language, cauda equina, and case reports. Data extraction was completed, and common findings were evaluated narratively due to heterogeneity of data. Results Seven manuscripts listed specific horse-related activities that caused SCI, with fall from horse as the highest percentage of injury. Nine articles identified the injury region, with large variations and no clear dominant area of injury. Five articles identified the length of hospital stay with ranges from 1 to 82 days. Four articles looked at the association of professional vs non-professional riders. Only two articles evaluated helmet use at time of injury, with one article showing 81% of those with SCI used helmets, and the other showing only 35.6% utilized this safety measure. Conclusion SCI in equestrian athletes can have a wide presentation, with large variation on location of injury, length of stay, and other factors. However, non-professional riders are at greater risk of SCI and individuals are more likely to sustain injury from a fall from a horse rather than a kick or another modality of injury. Future study can elicit presenting symptoms, types of surgical intervention used, and long-term outcomes and recovery.
Keywords: Equestrian